Short Communication: Species confirmation of juvenile cloudy grouper, Epinephelus erythrurus (Valenciennes, 1828), based on a morphologic analysis and partial CO1 gene sequencing - YANTI ARIYANTI; ACHMAD FARAJALLAH (Society for Indonesian Biodiversity, 2019)
Abstract. Ariyanti Y, Farajallah A. 2019. Species confirmation of juvenile cloudy grouper, Epinephelus erythrurus (Valenciennes, 1828), based on a morphologic analysis and partial CO1 gene sequencing. Biodiversitas 20: 914-921. The genus Epinephelus is the most species among the genera within the subfamily Epinephelinae. Species identification techniques for groupers, especially in the Epinephelus, are commonly based on color patterns and a suite of morphological characters, including body shape and the size and number of fins, scales and gill rakers. In some species, juveniles are morphologically distinct from adults of the same species, making morphological identification highly problematic. This present work will provide some morphological description or variations of juveniles that have been identified as Epinephelus erythrurus based on CO1 sequences. Further, the present study demonstrates that a molecular genetic technique, based on partial sequencing of the mitochondrial CO1 gene, may be used for the rapid species confirmation of every developmental stage and phase of an organism (juvenile E. erythrurus). Two DNA sequences of E. erythrurus from the Pangandaran District (7o43’8.31”S 108o30’11.59”E) have been submitted to GenBank under accession numbers KP998441 and KP998442.